Haar wavelet collocation method for solving boundary layer flow and heat transfer over a moving plate in a carbon nanotubes with MHD effect - N.S., Haswaniza; A.F.N., Rasedee; N., Bachok; T.J., Wong; M., Hasan (Lviv Polytechnic National University, 2025)
This study aims to explore the consideration of boundary layer flow and heat transfer over a moving plate with the presence of the magneto-hydrodynamics at the surface in carbon nanotubes. The mathematical model for the boundary layer flow problem is obtained and solved using numerical techniques based on Haar wavelet collocation. The types of nanoparticles used in this research were single-walled carbon nanotubes and multi-walled carbon nanotubes with water and kerosene that were used as base fluid. The partial differential equations are transformed into nonlinearly ordinary differential equations by similarity transformation. Maple software is used to work on these equations. The results were represented in the formation of graphs including velocity and temperature profile, skin friction coefficient and local Nusselt number for different values of magnetic field, CNTs volume friction and moving parameter. The outcomes obtained are that the moving plate gives non-unique solutions. In addition, the increments of magnetic field into the flow will increase value of skin friction coefficient and the heat transfer coefficient.